Analysis of Digital Content Service Levels on Customer Engagement and Sales Conversion in Digital Retail Businesses in Indonesia - Stepanus Dedy Deomedes (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The purpose of this study is to examine how the level of digital content service, consisting of the dimensions of quality, relevance, and delivery effectiveness, affects customer engagement and sales conversion in digital retail businesses in Indonesia. The measurement scale used a 1–5 Likert scale. The study measured all variable indicators from a questionnaire survey. The data were analyzed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) method, involving 300 respondents who were active users of local e-commerce platforms. The three dimensions of digital content service significantly influenced customer engagement and had a partial and significant direct effect on sales conversion. Customer engagement was proven to be a partial mediator of quality, relevance, and delivery effectiveness through conversion. The theoretical implications contribute to content-dependent digital marketing in the digital retail business in Indonesia.